Investigation of toxin genes among methicillin-resistant Staphylococcus aureus strains isolated from a tertiary hospital in Malaysia - Lim, K.T.; Hanifah, Y.A.; Mohd Yusof, M.Y.; Thong, Kwai Lin (Malaysian Society of Parasitology and Tropical Medicine, 2012)
Staphylococcus aureus is a persistent human pathogen responsible for a variety of infections ranging from soft-tissue infections to bacteremia. It produces a variety of virulence factors which are responsible for specific acute staphylococcal toxaemia syndromes. The objective of this study was to determine the prevalence of a repertoire of toxin genes among Malaysian MRSA strains and their genetic diversity by PCR-RFLP of coa gene. One hundred eighty-eight strains (2003, 2004, 2007 and 2008) of methicillin-resistant S. aureus (MRSA) were screened for 20 genes encoding for extracellular virulence determinant (sea, seb, sec, sed, see, seg, seh, sei, sej, tst, eta, etb, etd) and adhesins (cna, etb, fnbA, fnbB, hlg, ica, sdrE). The genetic relatedness of these strains was determined by PCR-RFLP of coa gene and agr grouping. Majority of the strains were tested positive for efb and fnbA (96% each), ica (78%) and hlg (59%) genes. A total of 101 strains were positive for at least one type of staphylococcal enterotoxin genes with sea being the predominant. Genes for seb, sed, see, seh, sej, eta and etb were not detected in any of the MRSA strains. The prevalence of sea, sec and ica among strains isolated in 2008 was increased significantly (p< 0.05) compared to 2003. Most of the strains were of agr type I (97.5%) followed by agr type II (1.2%) and agr type III (0.6%). All sea, sei and tst gene-positive strains were of agr type I. The only etd positive strain was agr type III. PCR-RFLP of coa produced 47 different patterns. The number of strains with virulence factors (sea, sec and ica) had increased over the years. No direct correlation between PCR-RFLP- coa profiles and virulotypes was observed.